An investigation into the mineralogy and processing characteristics of the Elsburg reefs at South Deep Gold Mine, South Africa - Notole, Viwe (My University, 2024)
Gold ores of the Witwatersrand Supergroup in South Africa are known to be amenable to metallurgical recovery through the process of cyanidation. However, the continuous decline in gold ore grade, increased environmental liability caused by residual cyanide in tailings and an increase in the complexity of ore composition calls for an alternative processing route. This is important to ensure that low-grade ore recovery is profitable while producing environmentally benign waste residue. Process mineralogy provides a systematic approach for the practical application of mineralogical knowledge, aiding ore characterisation and predictive behaviour, thus optimising how ores can best be mined, blended and processed. This study used mineralogical data and environmentally friendly leach reagent (i.e., glycine) to diagnose and predict processing characteristics of the composite Elsburg reefs at South Deep Gold Mine, South Africa. The mineralogy of these reefs is dominated by quartz and sulphide minerals, with pyrite, arsenopyrite, chalcopyrite and pyrrhotite being the common sulphides. More than 85% of gold in these reefs is locked or hosted in pyrite and quartz. The geochemistry shows high concentrations of siderophile (e.g., Cu, Ni and Co) and chalcophile (i.e., Cu and Zn) elements that can form stable complexes with glycine. A moderate to strong correlation of these elements (Cu, Co, Ni, Zn, etc.) with gold is conformable with the sulphide minerals-gold association. The poor liberation characteristics of Elsburg reefs ore and its geochemistry negatively influence gold recovery using glycine leaching. Sequential or multi-stage leaching is best to process ore with moderate to high Cu concentration and unliberated gold. The outcomes of this study demonstrate that Elsburg reefs gold ore responds well to sequential glycine leaching, with gold recoveries up to 95%, depending on which method or conditions are used. At low glycine dosage (e.g., 300 ppm), leaching duration of 50 hours, and ambient temperature (~23°C), bottle roll leaching of the Elsburg reefs yield low gold recovery (i.e., 30%), while at higher glycine dosage (e.g., 1500 ppm) and same leaching conditions (duration and temperature), a higher gold recovery (i.e., 41%) is attainable. Sequential leaching at a higher concentration of glycine (1500 ppm) with a leaching duration of 101 hours, yield cumulative gold recovery of up to 86%. Furthermore, at higher glycine concentration (1500 ppm) and elevated temperature (i.e., 40°C), Elsburg reefs yield considerably higher gold recovery (95%). The leaching solution was recharged at different time intervals from the beginning to the end of the leaching process. The increase in glycine was complemented by an increase in oxidant concentration (potassium permanganate). The ratio of potassium permanganate to glycine was kept at 2:1 (potassium permanganate: glycine).
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Gold ores; Mineralogy; South African mining